SOCIAL SUPPORT AS A DETERMINANT OF MOTHERS' PARENTING STYLES WITH TODDLERS - Yolanda Yolanda; Anggita Wijayanti; Jessica Tivanka; Agoes Dariyo (Journal of Social and Economics Research, 2026)
Family holds an important place in a person’s childhood, as parenting styles often determine a toddler’s successful growth and development. This study was done due to the low levels of parenting knowledge and the lack of social support found among mothers of toddlers in Benda Subdistrict, Tangerang City, Banten. The objective of this study is to identify the relationship between social support and their parenting styles. This quantitative correlational study was aided by 106 mothers of toddlers who were chosen through purposive sampling. Data was collected using the Multidimensional Scale of Perceived Social Support (MSPSS) and the Parenting Styles and Dimensions Questionnaire (PSDQ). The study results revealed a significant positive relationship between the two variables (r8 = 0.291; p = 0.002), with a medium effect size. Dimensional analysis indicated that social support had the strongest positive correlation with authoritative parenting (r8 = 0.313; p = 0.001). These findings confirm that there is a positive relationship between social support and parenting styles, particularly regarding the application of authoritative parenting. This suggests that the higher the level of adequate social support received, the more likely mothers are to adopt a warm, responsive, and structured approach in raising their children.